Comprehensive Diagnostic Evaluation of Cardiovascular Physiology in Patients With Pulmonary Vascular Disease: Insights From the PVDOMICS Program. (March 2020) - Tang, W. H. Wilson; Wilcox, Jennifer D.; Jacob, Miriam S.; Rosenzweig, Erika B.; Borlaug, Barry A.; Frantz, Robert P.; Hassoun, Paul M.; Hemnes, Anna R.; Hill, Nicholas S.; Horn, Evelyn M.; Singh, Harsimran S.; Systrom, David M.; et al.
Abstract : Background: Invasive hemodynamic evaluation through right heart catheterization plays an essential role in the diagnosis, categorization, and risk stratification of patients with pulmonary hypertension. Methods: Subjects enrolled in the PVDOMICS (Redefining Pulmonary Hypertension through Pulmonary Vascular Disease Phenomics) program undergo an extensive invasive hemodynamic evaluation that includes repeated measurements at rest and during several provocative physiological challenges. It is a National Institutes of Health/National Heart, Lung, and Blood Institute initiative to reclassify pulmonary hypertension groups based on clustered phenotypic and phenomic characteristics. At a subset of centers, participants also undergo an invasive cardiopulmonary exercise test to assess changes in hemodynamics and gas exchange during exercise. Conclusions: When coupled with other physiological testing and blood -omic analyses involved in the PVDOMICS study, the comprehensive right heart catheterization protocol described here holds promise to clarify the diagnosis and clustering of pulmonary hypertension patients into cohorts beyond the traditional 5 World Symposium on Pulmonary Hypertension groups. This article will describe the methods applied for invasive hemodynamic characterization in the PVDOMICS program. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02980887. Abstract : Supplemental Digital Content is available in the text.